Understanding the competitiveness implications of future phases of EU ETS on the industrial sectors - Ulrich Oberndorfer; Victoria Alexeeva-Talebi; Andreas Löschel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
In making key decisions for the future phases of the European Union Emissions Trading Scheme (EU ETS), policy makers need to fully understand the competitiveness implications of these decisions on industrial sectors. In this paper, we conduct an empirical analysis of cost pass-through ability of producers of selected products within the sectors refineries, glass, chemicals and ceramics of the UK economy. Our results provide new insights into the debate on the ability of pass-through of costs generated by the EU ETS. They suggest that some of the sectors analysed have the ability to pass-through a portion of their carbon costs to the consumers: The UK sectors are not capable to completely pass-through their costs into output prices, with the exception of UK ceramic goods.
Keywords: C22; D40; H23; 330; Emissions Trading; Competitiveness; Cost Pass-Through; Emissionshandel; EU-Umweltpolitik; Umweltschutzkosten; Verarbeitendes Gewerbe; Betriebliche Preispolitik; Internationaler Wettbewerb; Großbritannien